"Identify the expert": an experimental study in economic advice - Alysandratos, Theodore; Boukouras, Aristotelis; Geōrganas, Sōtērēs; Maniadis, Zacharias (SSRN, 2023)
In a set of preregistered experiments with general population, participants receive recommended answers to an economics questionnaire by two computerized advisors. One advisor is of high-accuracy (the Expert) and recommends the answers produced by academic consensus. The other advisor is of low accuracy (the Populist), and recommends the modal answers of participants from a pilot study. Participants do not know who the Expert is, and have to judge this from the recommendations. We examine which advisor participants identify as the Expert via revealed preference, i.e. participants select an advisor to answer the questionnaire on their behalf. We call this the `identify the Expert' problem. Our participants overwhelmingly choose the Populist, even when fully informed about the modus operandi of the two advisors. Bayesian models fail to explain these choices, even in the degenerate case where participants should be able to identify the Expert with 100% accuracy.